Dielectric, ferroelectric and induced strain behavior of PLZT 9/65/35 ceramics modified by Bi2O3and CuO co-doping - Siripong Somwan (2018)
© 2016 Elsevier Ltd and Techna Group S.r.l. PLZT 9/65/35 (Pb0.91La0.09(Zr0.65Ti0.35)0.9775O3) ceramics with addition of 0.25, 0.5 and 1.0 wt% of Bi2O3/CuO (where the ratio of Bi2O3:CuO=9:1 by mole) were prepared by sintering at the temperatures between 1000 and 1200 °C. It was found that Bi2O3/CuO could bring the sintering temperature down ~50 °C to obtain PLZT with no second phase. Dielectric and ferroelectric properties were investigated. Bi2O3/CuO decreased both coercive field and remnant polarization, which was caused by an increase of the degree of diffuseness in relaxor ferroelectric materials. Electric field induced strain behavior was also investigated and it was found that the addition of Bi2O3/CuO increased the maximum induced strain and maximized electrostrictive effect. Therefore, Bi2O3/CuO was useful as a sintering aid, which improved the dielectric and the relaxor ferroelectric properties as well as the electric field induced strain of PLZT ceramics.